The implementation of Secton Method for Solving Systems of Non Linear Equations - Nur Rokhman (Bandar Lampung University (UBL), 2013)
Newton method is a famous method for solving non linear equations numerically. This method is also suitable for solving systems of non linear equations. However, this method has a limitation because it requires the derivative of the non linear function which constructing the systems. The need of derivation some times lead to a problem. Secton method is a combination of Newton method and Secant method. Secton method omit the need of derivation of function. The performance of Secton method is almost same with Newton method. In this paper, Secton method is used to solve a non linear systems of equation. The experiments showed that Secton method could work well for solving non linear systems of equations.